EFEKTIVITAS MODEL PROBLEM BASED INSTRUCTION TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SDN BOJONGRENGED 1 - Nurhayati Sholihah, Ismi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Science learning in elementary schools is still dominated by conventional methods that do not actively engage students, resulting in low learning outcomes. This issue is also found at SDN Bojongrenged 1, Tangerang Regency, where most fourth-grade students have not achieved the Minimum Mastery Criteria (KKM). This study aims to analyze the effect of the Problem Based Instruction (PBI) learning model on science learning outcomes, particularly on the topic of